2007
DOI: 10.1007/s10840-007-9157-2
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of dilated cardiomyopathy by the elimination of frequent left or right premature ventricular contractions

Abstract: Elimination of frequent isolated PVC in patients with DCM with RF can normalize the clinical status and LV systolic function and dimensions, regardless of the morphology or origin of the PVC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 18 publications
1
51
0
3
Order By: Relevance
“…Other studies defined "frequent" PVCs as Ͼ10% of total beats rather than the absolute number of PVCs, 18,19 yet in some cases, a high PVC burden may not impair LV function, whereas PVC-induced cardiomyopathy can be observed in patients with lower PVC frequencies, albeit at lower incidences. 12,16,17 It is not known why the majority of patients with frequent PVCs have a benign course, whereas up to one third of them develop cardiomyopathy. One possible explanation is that the evaluation of PVC burden using 24-hour Holter monitoring may be inadequate and may misrepresent the patient's true PVC burden.…”
Section: Pvc Burdenmentioning
confidence: 99%
“…Other studies defined "frequent" PVCs as Ͼ10% of total beats rather than the absolute number of PVCs, 18,19 yet in some cases, a high PVC burden may not impair LV function, whereas PVC-induced cardiomyopathy can be observed in patients with lower PVC frequencies, albeit at lower incidences. 12,16,17 It is not known why the majority of patients with frequent PVCs have a benign course, whereas up to one third of them develop cardiomyopathy. One possible explanation is that the evaluation of PVC burden using 24-hour Holter monitoring may be inadequate and may misrepresent the patient's true PVC burden.…”
Section: Pvc Burdenmentioning
confidence: 99%
“…15) Some studies have reported that ablation of PVCs originating from the RV outflow tract resulted in reduction of the LV volume and improvement of the LV ejection fraction (LVEF). [16][17][18][19][20] The burden of PVCs has been reported to be correlated with the LVEF and known to be an independent predictive factor for worsening LV systolic function in patients with untreated frequent PVCs. 17,18,21) However, the burden of PVCs was not correlated with the volume of the cardiac chambers or the LVEF in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The success and complication rates for RFCA at our institute are comparable to that at other institutes. 16,[18][19][20] We excluded as many patients with potential confounding factors as possible and only 36 patients were analyzed in the current study. The strict exclusion of patients with potential confounding factors is a merit of this study, while the small sample size is a major limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Catheter ablation has emerged as an increasing popular option for these patients as the safety and efficacy profiles of the procedure have improved. Several studies have documented an improvement in LVEF following PVC ablation in nearly all patients along with significant reductions in LV enddiastolic dimensions of between 2 and 8 mm, mitral regurgitation by 75%, and New York Heart Association functional class by nearly 1 class (93,94,95). Significant improvement in radial, circumferential, and longitudinal strain after catheter ablation in patients with frequent PVCs and preserved LVEF has also been shown (96).…”
Section: Diagnosis and Managementmentioning
confidence: 95%